2020
DOI: 10.1177/2514848620934337
|View full text |Cite
|
Sign up to set email alerts
|

Green transformation is a boundary object: An analysis of conceptualisation of transformation in Norwegian primary industries

Abstract: The concept of green transformation is burgeoning in the academic literature and policy discourses, yet few empirical studies investigate what the concept actually means to diverse actors, and how it manifests in practices. This paper contributes to filling that gap. Through an analysis of policy documents and interviews, we investigate how central policy actors and interest organisations in Norwegian farming, fisheries and aquaculture conceptualise and enact transformation. The analysis of the policy document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…That's why the change efforts are being made today with real efforts towards green transformation. Amundsen and Hermansen (2020) found that differences in approach or level of change, in deep transformation and gradual change can be represented by threestage change. In the first stage of change, the status quo is protected, and only minor adjustments are made.…”
Section: Discussionmentioning
confidence: 99%
“…That's why the change efforts are being made today with real efforts towards green transformation. Amundsen and Hermansen (2020) found that differences in approach or level of change, in deep transformation and gradual change can be represented by threestage change. In the first stage of change, the status quo is protected, and only minor adjustments are made.…”
Section: Discussionmentioning
confidence: 99%
“…Major changes, inherent in ambitious sustainability targets, come with trade-offs between different values, groups, and activities, and therefore point to investigations on who prioritises what to understand what transformation may demand of different segments of society. Recent findings show that there is an obvious gap between how transformation is portrayed and pursued at the international level, at the national sectoral levels, and in locally based sectors (Amundsen & Hermansen, 2020). Understanding and applying local perceptions of societal transformation may be useful for revealing what different local actors view as meaningful and acceptable transformation directions .…”
Section: Theoretical and Methodological Approachesmentioning
confidence: 99%
“…The way how the narratives described above are grasped and reproduced by those in charge of creating and implementing the policies locally, play a key role in determining whether the spatialities in which the F-BB interact are reflected or not (Amundsen & Hermansen 2020). I will explore this argument in the following sections.…”
Section: Forest-based Bioeconomy As Regional Transformationmentioning
confidence: 99%
“…The case studies show that those narratives favour the transition of specific economic sectors but hide diverse socio-spatial configurations and, ultimately, downplay the role of the bioeconomy in a larger regional transformation (understood as a larger societal transformation that includes as much industrial modernisation and economic growth as civil society participation, social innovation and environmental justice). Empirical studies explaining how local and regional actors interpret and adapt green policies are still scarce (Amundsen & Hermansen 2020), and with this paper I intend to contribute to this debate. I begin with an overview of the multiple definitions given to the bioeconomy, paying special attention to the branch of the bioeconomy based on forest resources, as it is the dominant type of bioeconomy in Lapland, and gaining relevance in Catalonia.…”
Section: Introductionmentioning
confidence: 99%